2010
DOI: 10.3344/kjp.2010.23.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effect of Memantine and Morphine on Vincristine-induced Peripheral Neuropathy in Rats

Abstract: BackgroundVincristine-induced peripheral neuropathy is a major dose limiting side effect and thus effective therapeutic strategy is required. In this study, we investigated the antinociceptive effect of memantine and morphine on a vincristine-induced peripheral neuropathy model in rats.MethodsMale Sprague-Dawley rats weighing 220-240 g were used in all experiments. Rats subsequently received daily intraperitoneal injections of either vincristine sulfate (0.1 ml/kg/day) or saline (0.1 ml/kg/day) over 12 days, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
(43 reference statements)
1
25
1
Order By: Relevance
“…In this study, systemic morphine significantly Nouri et al 27 decreased pain responses in both phases of formalin in vincristine induced neuropathic test of 10 mg/kg, that is, similar results have been published with other models of neuropathic pain (Bulka et al, 2002;Erichsen et al, 2005;Park et al, 2010). In contrast, another study found opioid agonists, such as morphine (5 mg/kg, i.p.)…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In this study, systemic morphine significantly Nouri et al 27 decreased pain responses in both phases of formalin in vincristine induced neuropathic test of 10 mg/kg, that is, similar results have been published with other models of neuropathic pain (Bulka et al, 2002;Erichsen et al, 2005;Park et al, 2010). In contrast, another study found opioid agonists, such as morphine (5 mg/kg, i.p.)…”
Section: Discussioncontrasting
confidence: 51%
“…Better understanding of the underlying mechanisms is critical to allow identification of therapeutic targets, especially if these drugs produce their neurotoxic effects by mechanisms different from those by which they kill tumor cells (Park et al, 2010). Thus, although it is generally held that the therapeutic effects of vincristine is preventing tumor cell replication through alteration of cytoskeletal structure and disorientation of microtubules (Himes et al, 1976;Owellen et al, 1976), the mechanism by which they produce painful peripheral neuropathy, a major doselimiting side effect for this class of therapeutic agents, is not well understood (Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memantine, a 1-aminoadamantane derivative and an uncompetitive NMDA receptor antagonist, had an antinociceptive effect in the vincristine-induced peripheral neuropathy model in rats at a dose of 10 mg/kg [35]. Some derivatives of 1-aminoadamantane are investigated as potential analgesic compounds because of their agonist activity at CB 2 or/and CB 1 cannabinoid receptors [36] [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases have been also described of vincristine-induced CIPN with neuropathic pain, which are very distressing and painful with very difficult treatments. The study by by Park et al (2010) investigated the antinociceptive effect of memantine and morphine on a vincristine-induced CIPN model in rats. The authors concluded that systemic morphine and memantine have an antinociceptive effect in animal models.…”
Section: Antitubulins: Vinca Alkaloidsmentioning
confidence: 99%